2011
DOI: 10.1038/nnano.2011.36
|View full text |Cite
|
Sign up to set email alerts
|

A stretchable carbon nanotube strain sensor for human-motion detection

Abstract: Devices made from stretchable electronic materials could be incorporated into clothing or attached directly to the body. Such materials have typically been prepared by engineering conventional rigid materials such as silicon, rather than by developing new materials. Here, we report a class of wearable and stretchable devices fabricated from thin films of aligned single-walled carbon nanotubes. When stretched, the nanotube films fracture into gaps and islands, and bundles bridging the gaps. This mechanism allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

25
2,506
3
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 2,947 publications
(2,539 citation statements)
references
References 22 publications
25
2,506
3
5
Order By: Relevance
“…However, the Δ R / R 0 of a NTTF 5 @fiber sensor with ε pre = 1600% changed to be as large as 390 for ε = 1135%, and the GF was 21.3 for a strain range from 0% to 150% and 34.22 for a strain range from 200% to 1135%. The sensitivities over the whole strain range were better compared to those of previously reported highly stretchable strain sensors 28, 29, 30, 31, 32…”
mentioning
confidence: 67%
“…However, the Δ R / R 0 of a NTTF 5 @fiber sensor with ε pre = 1600% changed to be as large as 390 for ε = 1135%, and the GF was 21.3 for a strain range from 0% to 150% and 34.22 for a strain range from 200% to 1135%. The sensitivities over the whole strain range were better compared to those of previously reported highly stretchable strain sensors 28, 29, 30, 31, 32…”
mentioning
confidence: 67%
“…For instance, several studies have shown that CNTs networks can be formed within polymers to yield highly conductive and stretchable strain sensors 22, 207, 208, 216, 218, 219. In one paramount study, SWCNTs were embedded into a stacked nanohybrid structure within polyurethane (PU)–PEDOT:PSS to provide a transparent, stretchable, and patchable strain sensor 208.…”
Section: Conductive Polymer Compositesmentioning
confidence: 99%
“…For instance, they can be mounted on curved and dynamic surfaces of the skin to monitor the body's vital signs through real‐time/bilateral data transmissions based on a human–machine interface (HMI), thus realizing a hyperconnected society 8, 9, 10, 11, 12, 13. Commercial wearable devices exist predominantly in the form of patches, bands, and types of textiles that yield strains associated with motions and detaching stresses in the wrist, elbow, and waist, which requires stretchability over 10–20% 13, 14, 15, 16, 17…”
mentioning
confidence: 99%